Pengaruh e-Service Quality dan e-WOM terhadap Kepuasan Pengguna Shopee pada Ibu Rumah Tangga Pada Pembelian Produk Fashion - Alfifto, Alfifto (LPPM Universitas Buana Perjuangan Karawang, 2023)
The current development of e-commerce has given rise to numerous marketplaces in Indonesia, one of which is Shopee. Shopee is an online-based application that enables people to shop and acquire desired products at affordable prices without being constrained by distance or time limitations. Many applications are being developed as electronic commerce (e-commerce) based apps to be installed on smartphones and made accessible to people worldwide. Researchers selected Shopee due to its higher mention frequency among housewives in Tanjung Anom regarding online shopping, and they found Shopee easier to use compared to other marketplaces. Furthermore, the availability of offline shops selling fashion items is limited, with an insufficient variety of goods, and the distance from the mall to the Tanjung Anom area is considerable. This research stands out due to the scarcity of studies conducted on housewife respondents. Its objective is to assess the extent to which e-service quality and e-WOM impact customer satisfaction using the Shopee application. The study involved a sample of 85 respondents. The research approach employed is quantitative, utilizing the Accidental Sampling technique. Data processing involves multiple linear regression analysis using the SPSS software. The research findings indicate a relationship between the independent variables, namely e-service quality and e-WOM, and the dependent variable, customer satisfaction, either partially or collectively. The independent variables, encompassing e-service quality and e-WOM, jointly exert a positive and significant influence on customer satisfaction.